2013
DOI: 10.4161/cbt.26426
|View full text |Cite
|
Sign up to set email alerts
|

Berberine enhances radiosensitivity of esophageal squamous cancer by targeting HIF-1α in vitro and in vivo

Abstract: Radiation therapy is an important treatment approach for esophageal squamous cell carcinoma (ESCC). However, how to promote radiation sensitivity in ESCC remains a challenge. This study aimed to evaluate the effects of berberine, a common used Chinese medicine, on the radiosensitivity of ESCC. ECSS cell line ECA109 and TE13 were subjected to hypoxia and/or ionizing radiation (IR), in the presence or absence of berberine treatment. Cell growth and survival, and apoptosis were evaluated. In addition, ECA109 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 19 publications
5
37
0
Order By: Relevance
“…Furthermore, by exposing ESCC cells to hypoxia, we demonstrated that STAT3/HIF-1α/VEGF signaling pathway is involved in the radioresistance of ESCC, and stattic reverses the radioresistance by blocking STAT3/HIF-1α/VEGF signaling pathway. These results are in agreement with recent data that berberine increased the radiosensitivity of ESCC cells and xenografts via the inhibition of HIF-1α and VEGF expression [24].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, by exposing ESCC cells to hypoxia, we demonstrated that STAT3/HIF-1α/VEGF signaling pathway is involved in the radioresistance of ESCC, and stattic reverses the radioresistance by blocking STAT3/HIF-1α/VEGF signaling pathway. These results are in agreement with recent data that berberine increased the radiosensitivity of ESCC cells and xenografts via the inhibition of HIF-1α and VEGF expression [24].…”
Section: Discussionsupporting
confidence: 93%
“…The oxygen occurred during radiotherapy generates free oxygen radicals that induce DNA damage and kill tumor cells. 8,9 A hypoxic environment can stimulate the selection of locally or systemically aggressive tumor cell phenotypes by increased genomic instability, mutation and downregulation of DNA repair. 10 Under hypoxia, the homologous recombination (HR) pathway involved in DSB repair is compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia in tumors results from the imbalance between the increased oxygen consumption caused by extensive growth of tumor cells and poor oxygen delivery by disorganized tumor blood vessels (42). Drugs that target the hypoxia associated with resistance to radiation have had promising results (43). In the current study, paeonol caused marked downregulation of HIF-1α and VEGF in a dose-dependent manner with all tested radiation doses.…”
Section: Discussionmentioning
confidence: 51%